PENILAIAN KINERJA PELAYANAN BERBASIS SUMBER DAYA MANUSIA Di PERUSAHAAN DAERAH AIR MINUM Tirta Mon Pase Aceh Utara - Sufi Djakfar (Negotium: Jurnal Ilmu Administrasi Bisnis, 2018)
Performance Assessment of Human Resources-Based Services.This study aims to determine the performance of services and thedeterminants of the services performance at Regional WaterCompany (PDAM) in Tirta Mon Pase Regency. The method used isa qualitative approach, and the data were collected by interview,observation and documentation. Analysis of the data using thedomain analysis techniques. The results showed that theperformance of services at PDAM in Tirta Mon Pase are still low orless satisfactory. The deciding factor for poor performance ofservice, dominated by employees. The quantity of employeebehaviours are less. Moreover, their quality of the education levelis not in accordance with the nature and type of positionsassigned to the organization’s principal task at PDAM.